KEBIJAKAN PEMERINTAH TERHADAP PENGELOLAAN SAMPAH DI KELURAHAN EMPAGAE KECAMATAN WATTANG SIDENRENG KABUPATEN SIDENRENG RAPPANG TAHUN 2025 - Nur Fadilla Wadi (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to analyze government policies on waste management in Empagae Village, Wattang Sidenreng District, Sidenreng Rappang Regency. The main focus of this study is to identify the form of policy implemented and the factors that inhibit its implementation. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the waste management policy in the area has been designed through Regional Regulation Number 2 of 2024, which refers to the principle of 3R waste management (Reduce, Reuse, Recycle). However, its implementation still faces various obstacles, such as lack of supporting facilities, low public awareness, weak law enforcement, and limited participation of village officials. Using the Nvivo analysis tool, it was found that the management system implemented was not yet fully systematic, comprehensive, and sustainable. Therefore, improving infrastructure, community participation, and strengthening regulations are important factors to encourage the success of effective and sustainable waste management policies.